Features of the usage of the genotype-environment model in the individual selection of promising English oak (Quercus robur L.) genotypes in the Right-Bank Forest-Steppe - Нейко , І. С.; Нейко, О. В.; Василевський , О. Г.; Познякова , С. І.; Смашнюк , Л. В.; Єлісавенко , Ю. А.; Богословська , М. С.; Зленко , О. П. (Forestry and Forest Melioration, 2022)
Introduction Testing of plus trees’ progeny in Ukraine began in 1950–1960 by scientists of the Tree Breeding Laboratory of URIFFM under the leadership of S. S. Piatnytsky. At that time, the first progeny tests of the main forest tree species, in particular, English oak, were established. The progeny tests were created in certain regions and provided for the use of half-sib or sib progenies for 2–3 times. The first progeny test of English oak was planted by N. Davydova in 1958 in Kharkiv region. In 1976–1980, the investigation of plus trees progeny tests was led by V. Bilous in the Right-Bank Forest-Steppe. During that period, experimental oak stands were established under his leadership in identical conditions in Vinnytsia, Khmelnytskyi, and Ternopil regions. Nowadays, there is no possibility to assess the phenotypic and genotypic components of these stands. The article presents a theoretical generalization of the ecological and genetic approaches to the individual selection of promising genotypes based on the genotype-environment interaction model. The aim of the research was to define the most promising plus trees genotypes of English oak in the Right-Bank Forest-Steppe based on the indices of ecological plasticity and stability. Materials and Methods We used a set of indicators to assess the interaction between genotype and environment. At that, ecological models of two groups were applied: parametric and non-parametric. The European EUFGIS database was used when analysing the location of genetic units, both climatic and soil conditions. Ex situ gene pool conservation studies were conducted in Vinnytsia and Khmelnytskyi regions. The study was carried out in three plots of seedling seed orchards created in 2011. Results The highest height performance of trees was indicated in the site with the most southern location (B3). If the site were located in the northern part (C1), the average height of the progeny was 0.9 m. If progeny was moving to the south (B3), the average height increased to 2.7 m. The height increase made 1.8 m. While the average annual height increase in northern conditions was 0.12 m, in the southern part this indicator increases to 0.38 m. We calculated different indicators for the genotype-environment interaction model. Based on the environmental models, the best genotypes of English oak (Quercus robur L.) were selected. In terms of growth energy of the oak offspring (Q. robur) in the progeny tests of Vinnytsia and Ternopil regions, the predominance of genotypes of Vinnytsia (B-7, B-9, B-67) and Ternopil (T-13, T-15 and T-20) origins are characterized by high parameters of breeding estimation. The genotypes of plus trees of Vinnytsia (В-8, В-22, В-46, В-48, В-54, В-105) and Ternopil (Т-19) origins are more promising according to their parameters of ecological stability and growth energy. Conclusions When English oak progenies move from the north to the south, the share of phenotypic variability due to environmental conditions increases. Based on the indicators of ecological stability in environmental conditions and height growth energy, it was found that the best are the progenies of plus trees of Vinnytsia and Ternopil origins. The concept of testing plus trees should include a number of successive stages regarding their testing under a wide range of environmental conditions and subsequent analysis using the genotype-environment ecological model. 3 Figs., 7 Tables, 36 Refs.